Hemorrhagic cholecystitis: report of a case - Kwon, Jung-Nam (Korean journal of hepato-biliary-pancreatic surgery, 2012)
Hemorrhagic cholecystitis is an uncommon cause of abdominal pain that can be fatal. We report a case of hemorrhagic cholecystitis in a 75-year-old male taking an anticoagulant. The patient was brought to the hospital with uncontrolled right upper quadrant abdominal pain. On computed tomography, mild gallbladder wall thickening and high density with gallstones in the gallbladder suggested acute calculous cholecystitis or hemorrhagic cholecystitis. An urgent laparoscopic cholecystectomy was performed that revealed a gallbladder filled with large blood clots and two black stones. Patients who develop hemorrhagic complications were often receiving anticoagulation therapy or had pathologic coagulopathy. An early diagnosis of this potentially fatal condition is important to facilitate urgent surgical treatment.